A Religious State (A Study of Hasyim Asyari and Muhammad Iqbal's Thought on the Relation of Religion, State and Nationalism) - Arik Dwijayanto; Yusmicha Ulya Afif (UIN Sumatera Utara Medan, 2020)
This article explores the concept of a religious state proposed by two Muslim leaders: Hasyim Asyari (1871-1947), an Indonesian Muslim leader and Muhammad Iqbal (1873-1938), an Indian Muslim leader. Both of them represented the early generation when the emerging revolution for the independence of Indonesia (1945) from the Dutch colonialism and India-Pakistan (1947) from the British Imperialism. In doing so, they argued that the religious state is compatible with the plural nation that has diverse cultures, faiths, and ethnicities. They also argued that Islam as religion should involve the establishment of a nation-state. But under certain circumstances, they changed their thinking. Hasyim changed his thought that Islam in Indonesia should not be dominated by a single religion and state ideology. Hasyim regarded religiosity in Indonesia as vital in nation-building within a multi-religious society. While Iqbal changed from Indian loyalist to Islamist loyalist after he studied and lived in the West. The desire of Iqbal to establish the own state for the Indian Muslims separated from Hindus was first promulgated in 1930 when he was a President of the Muslim League. Iqbal expressed the hope of seeing Punjab, the North West province, Sind and Balukhistan being one in a single state, having self-government outside the British empire. In particular, the two Muslim leaders used religious legitimacy to establish political identity. By using historical approach (intellectual history), the relationship between religion, state, and nationalism based on the thinking of the two Muslim leaders can be concluded that Hasyim Asyari more prioritizes Islam as the ethical value to build state ideology and nationalism otherwise Muhammad Iqbal tends to make Islam as the main principle in establishment of state ideology and nationalism.Keywords: Hasyim Asyari, Muhammad Iqbal, religion, state, nationalism.